Understanding challenging behaviour as a social construction: exploring the role of pupil-teacher discourse in the secondary classroom - Stower, Hayley Emma (2017)
Challenging behaviour continues to be portrayed by the media, politicians and educationalist as a cause for concerns in UK secondary schools (DfE 2015, NASUWT, 2014). In recent years, there has been a shift in thinking amongst some researchers (Graff, 2009, Pomerantz, 2005) about how to view challenging behaviour in the classroom, recognising its idiographic nature. By drawing upon other disciplines, alongside psychology, social constructionist thinking has emerged as a helpful position from which to view challenging behaviour. From this position, challenging behaviour is socially constructed through language and action in the classroom.